TIPOLOGI STRATEGI PERENCANAAN SUMBER DAYA MANUSIA DALAM PERUSAHAN GLOBAL DENGAN EMPAT KUADRAN (DEVELOPMENT, EXPANSION, PRODUCTIVITY, DAN REDIRECTION) - Chandra, Advent; Haludin, Guntur; Ahmed, Galant Mohandirenza; Fernanda, Muhammad Raihan Rafi; Andhika, Muhammad Feby; Harianja, Tombang Daulat Niro; Herlambang, Dhafa (Gapenas Publisher, 2024)
Globalization has significantly changed the business landscape, forcing companies to face increasingly complex and diverse environments. Human resource management (HRM) becomes crucial in corporate strategy in the context of globalization. This study uses a qualitative method of systematic literature review to explain the typology of global HRM planning strategies with four quadrants (Development, Expansion, Productivity, and Redirection). The use of the Growth Readiness Matrix Approach can help companies manage HRM effectively amidst global market dynamics. Optimal HRM planning plays an important role in improving the quality of HRM, creating value for the company, and achieving competitive advantage in terms of the 4-quadrant strategy (Development, Expansion, Productivity, and Redirection).